Changes in perspective regarding Washington State Teacher Principal Evaluation Protocol (TPEP) - Amend, Michael Stephen (Kansas State University, 2023)
In this quantitative study, I surveyed building-level administrators in Washington State to see whether their perspectives regarding the Teacher-Principal Evaluation Program (TPEP) that was current in 2022 had changed since they had moved from classroom teaching to building administration. The research consisted of a survey with three primary parts. The first part consisted of questions to collect demographic information. The second part consisted of questions to collect information on current administrators’ perspectives regarding TPEP. The final section asked administrators to remember their experience being evaluated as a teacher and to answer the same questions from a teacher’s perspective. Specific perspectives examined included usefulness of the instrument for professional growth, impact on workload, impact on perception of career choice, and effectiveness of TPEP supports provided. Surveys were sent to all principals, assistant principals, and principal’s assistants in Washington State. Exclusion questions were included at the beginning of the survey to eliminate participants who did not have experience with TPEP as both an administrator and a teacher. I collected and analyzed data from each of the surveys to find descriptive statistics for each of the questions. Paired questions were then analyzed using a t-test to see whether any item had a statistically significant difference, using p < .05. Of the 24 questions analyzed, nine of those questions were found to have a statistically significant difference. Furthermore, of the nine questions showing a statistically significant difference, six of them were found in group H3, perception of workload. Of those six questions, all of them showed a more negative perspective from the administrator perspective than they did from the teacher perspective.
Keywords: Teacher Principal Evaluation Protocol; Teacher evaluation